VISUALISATION OF MICROGLIA WITH THE USE OF IMMUNOHISTOCHEMICAL DOUBLE STAINING METHOD FOR CD-68 AND Iba-1 OF CEREBRAL TISSUE SAMPLES IN CASES OF BRAIN CONTUSIONS - Stankov, Aleksandar; Belakaposka, Viktorija; Bitoljanu, Natasha; CHakar, LJupcho; Chakar, Zdravko; Rosoklija, Gorazd (Macedonian Academy of Sciences and Arts, 2015)
In the recent years it has been confirmed that the main component of the immune response in an injury of the nerve cell comes from microglia and macrophages. The main challenge in the field of microglia research is to detect the different stages of cellular activation by visualization of the cell morphology. The existing visualization techniques are based on surface molecules expression in resting and activated microglia cells. For visualization of the microglial cells and their functional state we used double labeling method for cd-68 and iba1 in brain contusions with different survival time. Microglia are stained brown with Iba-1, whereas microglia impregnated with black, grainy color, represents activated microglia stained with CD 68. We had significantly positive results, and we were able to observe changes in the morphology of the microglia that correlated with the survival time. Using double labeling with Iba-1 and cd68 we were able to determine their physiological state based on the morphology and immunoreactivity
Keywords: microglia cells; immunohistochemistry; brain contusions